A Compact Device Model for Nanoparticle-organic Memory Transistor’s Characterization - Mai, Huy Van; Bichler, Olivier; Gamrat, Christian; Viero, Yannick; Alibart, Fabien; Vuillaume, Dominique (Communications in Physics, 2018)
Neuromorphic electronic devices have recently been a candidate for new computing architecture associated with innovative nanotechnologies. A report of the characterization of Nanoparticle organic memory transistor (NOMFET) introduced a similar behavior to a biological spiking synapse in neural networks. In this paper, a refinement model based on the extracted parameters including a hybrid NOMFET/CMOS neuromorphic computing circuit and architecture of synapse to neuron interface by characterizing transistor -- memory and the temporal dynamic function is presented. A compact EKV model refinement serves as a link between nanotechnology process and circuit design for novel CMOS devices.